Pharmaceutical ethnobotany in the western part of Granada province (southern Spain): ethnopharmacological synthesis. - Benítez, G.; González-Tejero, M. R.; Molero-Mesa, J. (Journal of ethnopharmacology, 2010)
The aim of this work is to catalogue, document, and make known the uses of plants for folk medicine in the western part of the province of Granada (southern Spain). An analysis was made of the species used, parts of the plant employed, preparation methods, administration means, and the ailments treated in relation to pathological groups. Materials and methods: The work was performed in 16 municipalities within the study zone. The partici- pants were located mainly by questionnaires distributed in public and private centres. The information, gathered through semi-structured open interviews of a total of 279 people, was included in a database for subsequent analysis.Afloristic catalogue of the territorywascompiled, enabling analyses of the relevance of certain botanical families in popular medicine. Results and conclusions: Great diversity was established among medicinal species in the region. A total of 229 species of plants were catalogued for use in human medicine to prevent or treat 100 different health problems covering 14 different pathological groups. The number of references reached 1963. The popular pharmacopoeia of this area relies primarily on plants to treat digestive, respiratory, and circulatory problems, using mainly the soft parts of the plant (leavesandflowers)prepared in simpleways (decoction, infusion). An analysis of the medicinal ritual uses of 34 species and the different symptoms reflected a certain acculturation in relation to ethnobotanical knowledge in the last 20 years. Ethnopharmacological relevance: The traditional knowledge of plants was shown in relation to medicinal use, reflecting a striking diversity of species and uses, as well as their importance in popular plant therapy in the study zone. These traditions could pave the way for future phytochemical and pharmacological studies and thereby give rise to new medicinal resources.
The following values have no corresponding Zotero field: accession-num: 20226847
Keywords: Acculturation; Ethnopharmacology; Folk medicine; Granada; Medicinal plants; Spain